Pertumbuhan Luas Daun dan Kandungan Klorofil Pakcoy (Brassica rapa L.) pada Media Soilless Culture System (SCS) yang Diberi Kompos Bromelain dengan Induksi Inokulum Aspergillus sp. - Harfiani, Nabela H.N.; Irawan, Bambang; Mahfut, Mahfut; Nurcahyani, Endang (Jurusan Biologi FMIPA Universitas Cenderawasih, 2024)
The impact of drought on agricultural production is currently a major problem. Efforts to increase agricultural productivity are with modern agricultural systems that are efficient in the use of water, such as Soilless Culture System (SCS). This study was intended to identify the effectiveness and optimal dose of SCS planting media with the addition of bromelain compost induced by Aspergillus sp. to increase the growth of pakcoy (Brassica rapa L.) plants. This study used a completely randomized design method involving 4 SCS media treatments. The treatments applied involved the use of SCS media consisting of husks, vermicompost, and compost in the ratio of 3:2:1. Each treatment was differentiated by the addition of bromelain compost, namely P0= control (soil), P1= 3:2:1:2, P2= 3:2:1:3, and P3= 3:2:1:4, which had also been enriched with 1% Aspergillus sp. fungal inoculum. This study was conducted using 6 replications and involved 24 polybags with a volume of 1 kg/polybag. Parameters measured included leaf area and chlorophyll content. The findings of this study showed that bromelain compost induced by Aspergillus sp. inoculum had a significant impact on leaf area and leaf chlorophyll. The best result was P3 (3:2:1:4) treatment of 400 g/polybag which was better than other treatments on leaf area and leaf chlorophyll parameters. Key words: Aspergillus sp.; compost; pakcoy; Soilless Culture System (SCS); growing media.